Copper-based metal organic framework material as well as preparation method and application thereof

Through a simple one-step solvothermal method, a copper-based metal organic framework material with a two-dimensional nanolayered morphology with a petal-like arrangement was prepared, which solved the problem that the existing Cu-BTC structure was not conducive to the exposure of active sites, and significantly improved the efficiency of ethylene and ethanol Faraday in the electrocatalytic carbon dioxide reduction reaction.

CN119613741AActive Publication Date: 2025-03-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311177184.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

In the prior art, most of the structural units of Cu-BTC are octahedral micron-sized blocks with a pore size of about 1 nm, which is not conducive to mass transfer and exposure of active sites, resulting in low pore utilization, and limiting the efficiency of electrocatalytic carbon dioxide reduction reaction.

Method used

By a simple one-step solvothermal method, a copper-based metal organic framework material with a two-dimensional nanolayer morphology arranged in a petal shape is prepared, with the thickness of the nanolayer being 20-90 nm, preferably 20-50 nm. This method avoids complex conditions such as surfactants or two-phase interfaces, and is simple to operate and inexpensive.

Benefits of technology

This copper-based metal organic framework material has a high electrochemical activity area and catalytic activity. It is used in electrocatalytic reduction of carbon dioxide reactions, significantly improving the Faraday efficiency of ethylene and ethanol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613741A_ABST
    Figure CN119613741A_ABST
Patent Text Reader

Abstract

The invention relates to the field of preparation of metal organic framework materials, and discloses a copper-based metal organic framework material as well as a preparation method and application thereof. According to the copper-based metal organic framework material, the metal organic framework material has a nanometer layered morphology, and nanometer layers are distributed in a petal shape; wherein the metal element in the metal organic framework material is copper; an organic ligand in the metal organic framework material is trimesic acid. The copper-based metal organic framework material is used for electrocatalytic reduction of carbon dioxide, and has high ethylene and ethanol Faraday efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of metal organic framework materials, and in particular to a copper-based metal organic framework material and a preparation method and application thereof. Background Art

[0002] Global climate change is a major survival challenge facing mankind. Using renewable clean energy to capture and convert carbon dioxide through chemical methods is a very promising approach. Electrocatalytic carbon dioxide reduction technology uses renewable electricity to convert carbon dioxide into chemicals such as carbon monoxide, formic acid, methane, ethylene, ethanol, acetic acid and n-propanol to achieve resource utilization of carbon dioxide. Among them, ethylene and ethanol have both high energy density and market value, and are ideal products for electrocatalytic carbon dioxide reduction. However, at this stage, there is a lack of high-performance catalysts to support the development of electrocatalytic carbon dioxide reduction technology, so the development of high-performance catalysts is of great significance.

[0003] Metal organic framework (MOF) is a zeolite-like material formed by the complexation of organic ligands and metal ions. It has molecular / atomic catalytic active centers, high porosity, large surface area, high loading capacity and easy structural regulation, making it one of the most promising electrocatalytic carbon dioxide reduction catalysts. For example, copper-based metal organic framework materials Cu-BTC and its derivatives are often used for electrocatalytic carbon dioxide reduction. CN112301375A uses Cu-BTC to electrocatalytically reduce carbon dioxide, where the Faraday efficiency of ethylene can reach 30% and the Faraday efficiency of ethanol is less than 10%. Wolfgang Schuhmann et al. (DOI: 10.1002 / anie.202108313) used Cu-BTC as an electrocatalytic carbon dioxide reduction catalyst after carbonization and hydrophobic treatment. The sum of the Faraday efficiencies of ethylene and ethanol is less than 50%. Boon Siang Yeo et al. (DOI: 10.1021 / cs502128q) used electrodeposition technology to prepare cuprous oxide thin films for use as electrocatalytic carbon dioxide reduction catalysts. The sum of the Faraday efficiencies of ethylene and ethanol was less than 50%.

[0004] From the microscopic structure, the structural units of Cu-BTC in the prior art are mostly octahedral micron-sized blocks with a pore size of about 1nm, which is not conducive to mass transfer and exposure of active sites, and the pore utilization rate is low. The electrocatalytic carbon dioxide reduction reaction is a gas-liquid-solid three-phase interface reaction, which requires a catalyst with highly active sites exposed to promote the rapid adsorption of flowing carbon dioxide gas on the catalyst surface for reaction. Two-dimensional MOF materials expose abundant active centers and shorten the diffusion distance, which can well overcome the shortcomings of block MOFs.

[0005] Hua Chun Zeng et al. (DOI: 10.1002 / adfm.201505380) used polyvinyl pyrrolidone to regulate the arrangement of BTC, and used Cu2O with very low solubility as the copper source. The slowly released copper ion source and BTC were directional coordinated and polymerized to prepare a nanolayer with a thickness of 30nm to 55nm. CN108559101A disclosed that the bulk Cu-BTC was treated with alkali to break some coordination bonds and form nanolayers ranging from hundreds of nanometers. Jun Lin et al. (DOI: 10.1021 / acs.cgd.8b01695) dissolved copper ions in oleic acid to make the oleic acid encapsulate the copper ions, react with BTC in the aqueous phase at the interface between the two phases, inhibit the crystal growth rate and polymerization direction, and prepare spherical nanoparticles ranging from 30nm to 140nm.

[0006] At present, most of the preparation methods of two-dimensional Cu-BTC require the use of surfactants and other directional ligands to make metal ions and ligands polymerize in a directional manner; or control the direction of crystal growth through ligands with special structures; or layer the three-dimensional bulk layered materials through physical or chemical methods to form a two-dimensional nanolayer. However, there are shortcomings such as complex raw materials and harsh conditions, and new synthesis strategies are urgently needed. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems existing in the prior art and provide a copper-based metal organic framework material and its preparation method and application. The copper-based metal organic framework material of the present invention is used for the electrocatalytic reduction of carbon dioxide reaction and has a high Faraday efficiency of ethylene and ethanol.

[0008] In order to achieve the above-mentioned object, the present invention provides a copper-based metal organic framework material on one hand, wherein the metal organic framework material has a nano-layered morphology, and the nano-layers are distributed in a petal-like shape;

[0009] Wherein, the metal element in the metal organic framework material is copper;

[0010] The organic ligand in the metal organic framework material is trimesic acid.

[0011] A second aspect of the present invention provides a method for preparing a copper-based metal organic framework material, the method comprising the following steps:

[0012] (1) mixing a methanol solution of 2.5 hydrated copper nitrate with a methanol solution of trimesic acid to obtain a mixed solution; and subjecting the mixed solution to a hydrothermal reaction in a reaction vessel under closed conditions to obtain a solid product;

[0013] (2) washing and drying the solid product;

[0014] Wherein, the volume of the mixed liquid is 15-50% of the volume of the reaction container.

[0015] Preferably, the concentration of the methanol solution of 2.5 hydrated copper nitrate is 5-40 mg / mL, preferably 20-38 mg / mL.

[0016] Preferably, the concentration of the methanol solution of trimesic acid is 2-15 mg / mL, preferably 8-15 mg / mL.

[0017] The third aspect of the present invention provides a use of the copper-based metal organic framework material described in the first aspect or the copper-based metal organic framework material prepared by the preparation method described in the second aspect in an electrocatalytic reduction of carbon dioxide reaction.

[0018] Through the above technical solution, the beneficial effects of the present invention include:

[0019] The copper-based metal organic framework material with a two-dimensional nano-layered morphology arranged in a petal-like manner provided by the present invention has a high electrochemical active area and catalytic activity, and has a high Faraday efficiency for ethylene and ethanol when applied to the electrocatalytic reduction of carbon dioxide.

[0020] The preparation method of the copper-based metal organic framework material provided by the present invention can prepare a two-dimensional nanolayer with a petal-like arrangement by a simple one-step solvothermal method. The preparation process avoids the use of surfactants or the use of two-phase interfaces and insoluble precursors to reduce the growth rate. The operation is simple, the preparation conditions are mild, the cost is low, the synthesis method is efficient, and it is easy to scale up, so it has good application advantages and prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a scanning electron microscope image of the copper-based metal organic framework material prepared in Example 1 of the present invention;

[0022] Figure 2 It is the X-ray diffraction spectrum of the copper-based metal organic framework material prepared in Example 1 and Comparative Example 1 of the present invention;

[0023] Figure 3 is a scanning electron microscope image of the copper-based metal organic framework material prepared in Comparative Example 1 of the present invention;

[0024] Figure 4 is a scanning electron microscope image of the copper-based metal organic framework material prepared in Comparative Example 2 of the present invention;

[0025] Figure 5 This is a scanning electron microscope image of the copper-based metal organic framework material prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0026] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0027] In one aspect, the present invention provides a copper-based metal organic framework material, wherein the metal organic framework material has a nano-layered morphology, and the nano-layers are distributed in a petal-like manner;

[0028] Wherein, the metal element in the metal organic framework material is copper;

[0029] The organic ligand in the metal organic framework material is trimesic acid.

[0030] In the present invention, the petal-like distribution of the nanolayers means that the nanolayers are stacked on each other and radiate outwards in the shape of petals.

[0031] The morphology of the metal organic framework material of the present invention is measured by a scanning electron microscope.

[0032] According to the present invention, preferably, characterized by X-ray diffraction, the metal organic framework material has characteristic peaks at 2θ of 12.5°±0.2°, 21.6°±0.2°, 25.6°±0.2°, 32°±0.2°, 33.5°±0.2°, 34.4°±0.2°, 36°±0.2°, 41.6°±0.2° and 42.7°±0.2°.

[0033] It can be seen from the XRD spectrum that compared with the metal organic framework material of Comparative Example 1, the metal organic framework material of the present invention has characteristic peaks at 2θ of 12.5°±0.2°, 21.6°±0.2°, 25.6°±0.2°, 32°±0.2°, 33.5°±0.2°, 34.4°±0.2°, 36°±0.2°, 41.6°±0.2° and 42.7°±0.2°, which can be referred to Figure 2 The use of such a microstructured metal organic framework material is beneficial to improving the Faradaic efficiency of ethylene and ethanol in the subsequent electrocatalytic reduction of carbon dioxide.

[0034] According to the present invention, preferably, the thickness of the nanolayer is 20-90nm, preferably 20-50nm. This shows that the copper-based metal organic framework material of the present invention has a uniformly distributed two-dimensional nanolayer, and its thickness is concentrated. Compared with the micron-sized bulk Cu-BTC, the copper-based metal organic framework material of the present invention has more active sites exposed and can shorten the mass transfer distance. It is applied to the electrocatalytic reduction of carbon dioxide reaction, which is beneficial to improve the Faraday efficiency of ethylene and ethanol.

[0035] The thickness of the nanolayer of the present invention is obtained by observation using a scanning electron microscope.

[0036] A second aspect of the present invention provides a method for preparing a copper-based metal organic framework material, the method comprising the following steps:

[0037] (1) mixing a methanol solution of 2.5 hydrated copper nitrate with a methanol solution of trimesic acid to obtain a mixed solution; and subjecting the mixed solution to a hydrothermal reaction in a reaction vessel under closed conditions to obtain a solid product;

[0038] (2) washing and drying the solid product;

[0039] Wherein, the volume of the mixed liquid is 15-50% of the volume of the reaction container.

[0040] In the preparation method provided by the present invention, a specific methanol solution of 2.5 hydrated copper nitrate is combined with a methanol solution of trimesic acid, and the filling degree of the mixed solution in the reaction container is controlled to prepare the two-dimensional nanolayer arranged in a petal shape as described in the first aspect of the present invention. The two-dimensional nanolayer arranged in a petal shape as described in the present invention has a high electrochemical active area and catalytic activity, and is applied to the electrocatalytic reduction of carbon dioxide reaction and has a high Faraday efficiency of ethylene and ethanol.

[0041] The present invention has no particular limitation on the reaction vessel of the hydrothermal reaction in step (1), and it can be any container that can realize the hydrothermal reaction. The present invention uses a conventional hydrothermal reactor with a polytetrafluoroethylene liner as an example.

[0042] In the prior art, under the premise of ensuring the safety of the reaction, the volume of the mixed solution in the reaction container is generally as large as possible to obtain more metal organic framework materials. Usually, the volume of the mixed solution is 70-80% of the volume of the reaction container. In the present invention, the volume of the mixed solution is 15-50% of the volume of the reaction container, preferably 20-40%, for example, it can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, and any value in the range formed by any two of these values. The use of this preferred embodiment is conducive to methanol vapor reducing the coordinated divalent copper nodes to cuprous, and forming a unique two-dimensional layered nanostructure and a new crystal structure after recrystallization.

[0043] According to the present invention, preferably, the concentration of the methanol solution of 2.5 hydrated copper nitrate is 5-40 mg / mL, preferably 20-38 mg / mL, for example, it can be 5 mg / mL, 8 mg / mL, 10 mg / mL, 12 mg / mL, 14 mg / mL, 16 mg / mL, 18 mg / mL, 20 mg / mL, 22 mg / mL, 24 mg / mL, 26 mg / mL, 28 mg / mL, 30 mg / mL, 32 mg / mL, 34 mg / mL, 36 mg / mL, 38 mg / mL, 40 mg / mL, and any value in the range formed by any two of these values. Adopting this preferred embodiment is conducive to obtaining the copper-based metal organic framework material of the morphology and distribution described in the present invention.

[0044] According to the present invention, preferably, the concentration of the methanol solution of trimesic acid is 2-15 mg / mL, preferably 8-15 mg / mL, for example, it can be 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, and any value in the range formed by any two of these values. The use of this preferred embodiment is conducive to obtaining the copper-based metal organic framework material with the morphology and distribution described in the present invention.

[0045] According to the present invention, preferably, the mass ratio of 2.5 hydrated copper nitrate to trimesic acid is 0.4-6, preferably 1.5-3, for example, it can be 0.4:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, and any value in the range formed by any two of these values. The use of this preferred embodiment is more conducive to obtaining the copper-based metal organic framework material with the morphology and distribution described in the present invention.

[0046] The present invention has no particular limitation on the mixing in step (1), and the mixing can be carried out according to conventional methods in the art.

[0047] According to the present invention, preferably, the conditions of the hydrothermal reaction in step (1) include: a temperature of 80-130°C, preferably 110-125°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, and any value in the range formed by any two of these values; a time of 12-60h, preferably 18-36h, for example, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 44h, 46h, 48h, 50h, 52h, 54h, 56h, 58h, 60h, and any value in the range formed by any two of these values. The use of this preferred embodiment is beneficial to improving the Faradaic efficiency of ethylene and ethanol in the subsequent electrocatalytic reduction of carbon dioxide reaction.

[0048] Preferably, the method further comprises: performing solid-liquid separation on the product of the hydrothermal reaction in step (1) to obtain a solid product.

[0049] The present invention has no particular limitation on the method of solid-liquid separation, and the solid-liquid separation can be carried out by conventional technical means in the art.

[0050] The present invention has no particular limitation on the specific conditions of the washing, and the washing can be carried out according to methods in the art until the solution is clear.

[0051] The present invention has a wide range of choices for the type of detergent for washing, which can be a conventional choice in the art. Preferably, the detergent for washing is selected from at least one of water, methanol, ethanol and acetone.

[0052] According to a specific embodiment of the present invention, the solid product is washed with a detergent and soaked in the detergent for 1-2 days, and the anhydrous ethanol is replaced 2-5 times during the soaking period. This preferred embodiment is conducive to fully removing unreacted substances.

[0053] The present invention has no particular limitation on the drying conditions of step (2), and the drying can be carried out according to methods in the art. Preferably, the drying is vacuum drying.

[0054] Preferably, the method does not include adding a surfactant. The surfactant can be a conventional choice in the art, and the present invention will not be described in detail here.

[0055] By adopting this preferred embodiment, the preparation method provided by the present invention avoids substances such as surfactants, is simple to operate, has mild preparation conditions, is low in cost, has an efficient synthesis method, is easy to scale, and has good application advantages and prospects.

[0056] The third aspect of the present invention provides a use of the copper-based metal organic framework material described in the first aspect or the copper-based metal organic framework material prepared by the preparation method described in the second aspect in an electrocatalytic reduction of carbon dioxide reaction.

[0057] The present invention has no particular limitation on the conditions for the electrocatalytic reduction of carbon dioxide reaction, and the reaction can be carried out according to conventional methods in the art.

[0058] The present invention will be described in detail below through examples.

[0059] In the following examples, the detection method of the product is as follows:

[0060] Gas product analysis: A gas chromatograph (Agilent 7890B) was used, equipped with a hydrogen ion flame detector and a thermal conductivity detector. The thermal conductivity detector detected hydrogen, and carbon monoxide was detected by the hydrogen ion flame detector after hydrogenation in the methane reformer.

[0061] Liquid product analysis: Using hydrogen nuclear magnetic resonance (Agilent 700M), take the cathode electrolyte, add heavy water to lock the field, and use dimethyl sulfoxide as the internal standard.

[0062] Example 1

[0063] Take 0.451g of 2.5 hydrated copper nitrate and dissolve it in 15mL methanol to prepare solution A; dissolve 0.220g of trimesic acid in 15mL methanol to prepare solution B; mix solution A and solution B to obtain a mixed solution. Transfer the mixed solution to a 100mL polytetrafluoroethylene-lined stainless steel jacket hydrothermal reactor, react at 120℃ for 24h, and then cool to room temperature. The reaction product of the hydrothermal reaction is separated from the solid and liquid to obtain a solid product.

[0064] The solid product was washed with anhydrous ethanol and soaked in anhydrous ethanol for 2 days, during which the anhydrous ethanol was replaced 4 times. The washed material was then vacuum dried at 80° C. for 12 h to obtain a copper-based metal organic framework material.

[0065] The SEM image of the copper-based metal organic framework material described in Example 1 is given as an example. Figure 1 As shown. It can be seen that the copper-based metal organic framework material has a nano-layered morphology, such as Figure 1 As shown in b, the thickness of the nanolayer is 30-50 nm, and the nanolayer is distributed in a petal-like shape, as shown in Figure 1 As shown in a.

[0066] The XRD pattern of the copper-based metal organic framework material described in Example 1 is given as an example. Figure 2 As shown. It can be seen that compared with Comparative Example 1, the petal-shaped Cu-BTC of Example 1 has diffraction peaks at diffraction angles of 12.5°, 21.6°, 25.6°, 32°, 33.5°, 34.4°, 36°, 41.6° and 42.7°, indicating the formation of a new phase, and the crystal structure of the petal-shaped Cu-BTC of Example 1 has changed significantly.

[0067] Example 2

[0068] Take 0.451g of 2.5 hydrated copper nitrate and dissolve it in 15mL methanol to prepare solution A; dissolve 0.174g of trimesic acid in 15mL methanol to prepare solution B; mix solution A and solution B to obtain a mixed solution. Transfer the mixed solution to a 100mL polytetrafluoroethylene-lined stainless steel jacket hydrothermal reactor, react at 110℃ for 24h, and then cool to room temperature. The reaction product of the hydrothermal reaction is separated from the solid and liquid to obtain a solid product.

[0069] The solid product was washed with anhydrous ethanol and soaked in anhydrous ethanol for 2 days, during which the anhydrous ethanol was replaced 4 times. The washed material was then vacuum dried at 80° C. for 12 hours to obtain a copper-based metal organic framework material with a nanolayer thickness of 30-50 nm.

[0070] Example 3

[0071] Take 0.400g of 2.5 hydrated copper nitrate and dissolve it in 20mL methanol to prepare solution A; dissolve 0.161g of trimesic acid in 20mL methanol to prepare solution B; mix solution A and solution B to obtain a mixed solution. Transfer the mixed solution to a 100mL polytetrafluoroethylene-lined stainless steel jacket hydrothermal reactor, react at 110℃ for 36h, and then cool to room temperature. Separate the reaction product of the hydrothermal reaction into solid and liquid to obtain a solid product.

[0072] The solid product was washed with anhydrous ethanol and soaked in anhydrous ethanol for 2 days, during which the anhydrous ethanol was replaced 4 times. The washed material was then vacuum dried at 80° C. for 12 hours to obtain a copper-based metal organic framework material with a nanolayer thickness of 30-50 nm.

[0073] Example 4

[0074] The method of Example 1 is followed, except that 0.206 g of 2.5 hydrated copper nitrate is dissolved in 8 mL of methanol to prepare solution A; 0.101 g of trimesic acid is dissolved in 8 mL of methanol to prepare solution B; solution A and solution B are mixed to obtain a mixed solution. The volume of the mixed solution is 16% of the volume of the reaction container, and a copper-based metal organic framework material is obtained, and the thickness of the nanolayer is 30-50 nm.

[0075] Example 5

[0076] The method of Example 1 is followed, except that the amount of 2.5 hydrated nitric acid used is 0.3 g, to obtain a copper-based metal organic framework material, and the thickness of the nanolayer is 30-50 nm.

[0077] Example 6

[0078] The method of Example 1 was followed, except that the amount of trimesic acid used was 0.42 g, to obtain a copper-based metal organic framework material with a nanolayer thickness of 30-50 nm.

[0079] Example 7

[0080] The method of Example 1 was followed, except that the temperature of the hydrothermal reaction was 130° C. to obtain a copper-based metal organic framework material, and the thickness of the nanolayer was 25-45 nm.

[0081] Example 8

[0082] The method of Example 1 was followed, except that the reaction time of the hydrothermal reaction was 12 h, to obtain a copper-based metal organic framework material, and the thickness of the nanolayer was 30-50 nm.

[0083] Comparative Example 1

[0084] Copper-based metal organic framework material prepared by prior art

[0085] Take 2.952g of copper nitrate trihydrate and dissolve it in 40.5mL of ethanol aqueous solution (ethanol: water volume ratio is 1:1) to prepare solution A; dissolve 1.713g of trimesic acid in 40.5mL of ethanol aqueous solution (ethanol: water volume ratio is 1:1) to prepare solution B; after mixing solution A and solution B at room temperature, transfer them into a 100mL polytetrafluoroethylene-lined stainless steel jacket reactor, react at 120°C for 24h, cool to room temperature after the reaction is completed, separate the reaction product of the hydrothermal reaction to obtain a solid product.

[0086] The solid product was washed with anhydrous ethanol and then soaked in anhydrous ethanol for two days, during which the anhydrous ethanol was replaced several times. The washed material was then vacuum dried at 80° C. for 12 h to obtain a copper-based metal organic framework material, which was recorded as Cu-BTC.

[0087] The scanning electron microscope picture of comparative example 1 is as follows Figure 3 As shown, the obtained product is a classic octahedral block.

[0088] The XRD pattern of the copper-based metal organic framework material described in Comparative Example 1 is as follows: Figure 2 As shown, it can be seen that it is consistent with the Cu-BTC crystal structure reported in existing literature.

[0089] Comparative Example 2

[0090] The method of Example 1 is followed, except that an equal mass of copper nitrate trihydrate is used instead of 2.5 hydrated copper nitrate to obtain a copper-based metal organic framework material.

[0091] The SEM image of the copper-based metal organic framework material described in Comparative Example 2 is as follows: Figure 4 As shown. Figure 4 The product shown is formed by a small amount of nanolayers and a large amount of bulk agglomeration, and does not show the Figure 1 The uniform petal-shaped two-dimensional nanolayer structure shown.

[0092] Comparative Example 3

[0093] The method of Example 1 was followed, except that 0.644 g of 2.5 hydrated copper nitrate was dissolved in 25 mL of ethanol to prepare solution A, and 0.314 g of trimesic acid was dissolved in 25 mL of ethanol to prepare solution B, to obtain a copper-based metal organic framework material.

[0094] The SEM image of the copper-based metal organic framework material described in Comparative Example 3 is as follows: Figure 5 As shown in FIG. 1 , it can be seen that the obtained product is a micron-sized block formed by agglomeration of nanoparticles.

[0095] Test Example 1

[0096] 5 mg of the copper-based metal organic framework material prepared in the embodiment and the comparative example were dispersed in 500 μL of anhydrous ethanol, ultrasonicated for 15 min, 20 μL of perfluorosulfonic acid resin Nafion solution was added, ultrasonicated for 30 min to obtain a mixed solution, 60 μL of the mixed solution was drop-coated on 1 cm × 1 cm carbon paper (Japan Toray hydrophobic carbon paper), dried at 40 ° C, and a working electrode loaded with copper-based metal organic framework material was obtained, wherein the loading of the copper-based metal organic framework material was 0.58 mg. A 1 cm × 1 cm platinum sheet was used as a counter electrode, Ag / AgCl (saturated KCl) was used as a reference electrode, a proton exchange membrane (Nafion 117) separated the anode and cathode chambers, and selectively entered the cathode chamber through the anode cation, and a 0.1 M KHCO3 solution was used as an electrolyte, and an electrocatalytic carbon dioxide reduction test was performed in a three-electrode system H-type electrolytic cell composed of the above components. Pure carbon dioxide gas was used as the reactant, the gas mass flowmeter controlled the gas flow rate to be 50 mL / min, and the reaction was performed for 60 min at a potential of -1.6 (V vs reversible hydrogen electrode), as shown in Table 1.

[0097] Table 1

[0098]

[0099]

[0100] It can be seen from the results in Table 1 that the copper-based metal organic framework material provided by the present invention is applied to the electrocatalytic carbon dioxide reduction reaction, which has significantly higher Faraday efficiency of ethylene and ethanol.

[0101] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A copper-based metal organic framework material, characterized in that: The metal organic framework material has a nano-layered morphology, and the nano-layers are distributed in a petal-like manner; Wherein, the metal element in the metal organic framework material is copper; The organic ligand in the metal organic framework material is trimesic acid.

2. The metal organic framework material according to claim 1, wherein Characterized by X-ray diffraction, the metal organic framework material has characteristic peaks at 2θ of 12.5°±0.2°, 21.6°±0.2°, 25.6°±0.2°, 32°±0.2°, 33.5°±0.2°, 34.4°±0.2°, 36°±0.2°, 41.6°±0.2° and 42.7°±0.2°.

3. The metal organic framework material according to claim 1 or 2, wherein: The thickness of the nanolayer is 20-90 nm, preferably 20-50 nm.

4. A method for preparing a copper-based metal organic framework material, the method comprising the following steps: (1) mixing a methanol solution of 2.5 hydrated copper nitrate with a methanol solution of trimesic acid to obtain a mixed solution; and subjecting the mixed solution to a hydrothermal reaction in a reaction vessel under closed conditions to obtain a solid product; (2) washing and drying the solid product; Wherein, the volume of the mixed liquid is 15-50% of the volume of the reaction container.

5. The method according to claim 4, wherein: The volume of the mixed solution is 20-40% of the volume of the reaction container.

6. The method according to claim 4, wherein: 2.5 The concentration of the methanol solution of hydrated copper nitrate is 5-40 mg / mL, preferably 20-38 mg / mL; And / or, the concentration of the methanol solution of trimesic acid is 2-15 mg / mL, preferably 8-15 mg / mL.

7. The method according to claim 4, wherein: The mass ratio of 2.5 hydrated copper nitrate to trimesic acid is 0.4-6, preferably 1.5-3.

8. The method according to any one of claims 4 to 7, wherein: The conditions of the hydrothermal reaction in step (1) include: temperature of 80-130° C., preferably 110-125° C.; time of 12-60 h, preferably 18-36 h.

9. The method according to any one of claims 4 to 7, wherein: The washing agent for washing is selected from at least one of water, methanol, ethanol and acetone.

10. Use of the copper-based metal organic framework material according to any one of claims 1 to 3 or the copper-based metal organic framework material prepared by the preparation method according to any one of claims 4 to 9 in the electrocatalytic reduction of carbon dioxide.

Citation Information

Patent Citations

  • Method for preparing two-dimensional sheet-shaped Cu-MOF (Metal Organic Framework) material

    CN108559101A

  • Graphene-metal organic framework composite material modified electrode preparation method

    CN107703195A

  • Preparation method for constructing two-dimensional metal-organic frameworks (MOFs) nano-hydrolysis electrocatalyst based on foamy copper and application of two-dimensional MOFs nano-hydrolysis electrocatalyst to water electrolysis for hydrogen evolution

    CN109518220A

  • Carbon dioxide electrochemical reduction catalyst, preparation method and applications thereof

    CN110918112A

  • Metal organic framework composite material and preparation method and application thereof

    CN111266089A